1992
DOI: 10.1080/00102209208947158
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study on Pyrolysis and Oxidation of CH3Cl in Ar/H2/O2Mixtures

Abstract: The thermal decomposition of methyl chloride in hydrogen/oxygen mixtures and argon bath gas was carried out at I atmosphere pressure in tubular flow reactors. CH,CI, intermediate, and final products were analyzed over the temperature range 1098 to 1273 K, with average residence times of 0.2 to 2.0s.A detailed kinetic reaction mechanism based upon fundamental thermochemical and kinetic principles, Transition State Theory and evaluated literature rate constant data was developed to explain and understand the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 12 publications
2
47
0
Order By: Relevance
“…The Cl attack enhances CH 4 conversion and some organic intermediates are produced [26]: It is shown that the pollutants emission may be lower if CH 4 is combusted first and then CCl 4 is injected into the high temperature flue gas, rather than directly mixing the CCl 4 with CH 4 before combustion, which means a two-stage combustion mode. At the first stage, CH 4 will be oxidized to CO 2 and H 2 O, and the inhibition of chlorine on CH 4 oxidation could be eliminated.…”
Section: Discussion Of the Interaction Mechanism Between CCL 4 And Chmentioning
confidence: 99%
“…The Cl attack enhances CH 4 conversion and some organic intermediates are produced [26]: It is shown that the pollutants emission may be lower if CH 4 is combusted first and then CCl 4 is injected into the high temperature flue gas, rather than directly mixing the CCl 4 with CH 4 before combustion, which means a two-stage combustion mode. At the first stage, CH 4 will be oxidized to CO 2 and H 2 O, and the inhibition of chlorine on CH 4 oxidation could be eliminated.…”
Section: Discussion Of the Interaction Mechanism Between CCL 4 And Chmentioning
confidence: 99%
“…Numerical calculations were conducted to model silica generation and possible changes in flame structure with the silica generation. Reaction mechanism consists of 19 species and 43 reaction steps including 19 oxyhydrogen reactions [15] and 19 reactions related to chlorinated species [16] as well as silica formation reactions via oxidation [17] and hydrolysis [18] of SiCl 4 , as listed in Table 2. Governing equations and numerical schemes have been presented in Lee and Chung [19] and Smooke [20].…”
Section: Experiments and Numerical Analysismentioning
confidence: 99%
“…(See, for example, , Chang and Senkan 1989, Fisher et al 1990, and Ho et al 1992 For such modeling studies, however, it is required that the rate parameters of a large number of reactions be estimated. Although estimation in itself is not undesirable, as there will always be more reactions in such complex systems than resources available to study them individually in isolated experiments, experimental rate measurements on reactions of chlorinated species at combustion temperatures serve as vital references to assess the validity of predictions and to calibrate theoretical methods.…”
mentioning
confidence: 99%